Limited Shared Variance among Measures of Cognitive Performance Used in Nutrition Research: The Need to Prioritize Construct Validity and Biological Mechanisms in Choice of Measures. Issue 5 (26th April 2021) - Wenger, Michael J; DellaValle, Diane M; Todd, Lauren E; Barnett, Amy L; Haas, Jere D
ABSTRACT: Background: The literature on correlates of nutrition has seen an increase in studies focused on functional consequences at the levels of neural, perceptual, and cognitive functioning. A range of measurement methodologies have been used in these studies, and investigators and funding agencies have raised the questions of how and if these various methodologies are at all comparable. Objective: The aim was to determine the extent to which 3 different sets of cognitive measures provide comparable information across 2 subsamples that shared culture and language but differed in terms of socioeconomic status (SES) and academic preparation. Methods: A total of 216 participants were recruited at 2 US universities. Each participant completed 3 sets of cognitive measures: 1 custom-designed set based on well-understood laboratory measures of cognition [cognitive task battery (COGTASKS)] and 2 normed batteries [Cambridge Neuropsychological Test Automated Battery (CANTAB), Weschler Adult Intelligence Scale, fourth edition (WAIS-IV)] designed for assessing general cognitive function. Results: The 3 sets differed with respect to the extent to which SES and educational preparation affected the results, with COGTASKS showing no differences due to testing location and WAIS-IV showing substantial differences. There were, at best, weak correlations among tasks sharing the same name or claiming to measure the same construct. Conclusions: Comparability of measures of cognition cannot be assumed, even if measures have the same name or claim to assess the same construct. In selecting and evaluating different measures, construct validity and underlying biological mechanisms need to be at least as important as population norms and the ability to connect with existing literatures.